2022
DOI: 10.47203/ijch.2022.v34i01.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of needle stick injuries, its associated factors and awareness among nursing staff at tertiary care hospital of North India

Abstract: Background: Needle Stick Injuries (NSIs) are defined as accidental skin penetrating injuries caused by needles. It is the single greatest occupational hazard to a medical personnel. In developing countries, needle stick injury is associated with the highest global prevalence of HIV, Hepatitis B, and Hepatitis C. Aim & Objectives: To estimate the prevalence of needle stick injuries, its associated risk factors and assess the awareness regarding needle stick injuries among nursing staff. Material & Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…10,12,[14][15][16] North India by Bharti (66.7%) and Ashat (68.2%). 17,18 But the overall prevalence in this study is lower than the figure from an earlier study in Iran by Jahangiri (76%). 19,20 Whereas, slightly lower prevalence was reported from Tehran (Iran) by Galougahi (56.96%), Assam (India) by Gupta (53.7%).…”
Section: Prevalence Of Needle Stick Injury In Staff Nursescontrasting
confidence: 81%
See 1 more Smart Citation
“…10,12,[14][15][16] North India by Bharti (66.7%) and Ashat (68.2%). 17,18 But the overall prevalence in this study is lower than the figure from an earlier study in Iran by Jahangiri (76%). 19,20 Whereas, slightly lower prevalence was reported from Tehran (Iran) by Galougahi (56.96%), Assam (India) by Gupta (53.7%).…”
Section: Prevalence Of Needle Stick Injury In Staff Nursescontrasting
confidence: 81%
“…14 Bharti in contrast reported that the chances of getting NSI were higher among married staff nurses in comparison to the unmarried nursing staff. 17 Regarding sex, our study showed no significant association between gender and needle stick injury. Similar results have also been reported by Ahmed.…”
Section: Demographic Variables and Other Risk Factors Associated With...contrasting
confidence: 58%
“…Majority of NSI incidents were observed in nursing staff having 4–6 years (70.5%) of experience and there was a decreasing trend with increase in years of experience. A similar inference was made by Bharti et alin their study in which nursing staff had 1.66 times higher chances of needle stick injury than those who had working experience more than 10 years ( 8 ). Dille et al also had same inference (0–5 years, 75.1%) ( 2 ).…”
Section: Discussionsupporting
confidence: 69%
“…The overall NSI prevalence in our study is 51.6% (49/95) which is higher than that reported from 2 Indian studies by Bhargava et al (44%) and Sardesai et al (45%) ( 6 , 7 ). Bharti et al and Gupta et al reported a prevalence of 66.7% and 69% respectively ( 3 , 8 ). Approximately 11.5% nursing staff reported more than one NSI event in their life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation